Between The Indonesian Bankruptcy Law and Fiqh Ibnu Qudamah’s about Ahkam Iflas in Al-Mughni - Muhammad Rusydianta (Al-Muamalat: Journal of Islamic Economics Law, 2025)
ENGLISH Research Main Problem: This article begin from the researchers similarities finding, such as Lubis found that various bankruptcy provisions in Bidayatu Al-Mujtahid are similar to Indonesian Bankruptcy Law, and Western bankruptcy regulations (Common Law and Civil Law) as Abed and Michael found in their research, Al-Mughni’s bankruptcy provisions (Ibn Qudamah’s book) similar with the United States Bankruptcy Act. Then, it might be worth examining Indonesian Bankruptcy Law in comparison with Ibn Qudamah’s fiqh;  Research Objectives: To discover the similar post-modern bankruptcy provisions analogous to Islamic Law “ahkam iflas” discussed in Ibn Qudamah’s book since eighth century earlier. Especially, how does the legal substance of iflas in this work of jurists compare with Law No. 37 of 2004 concerning Bankruptcy and Delayment of Debt Payment Obligations; Methodology: Utilising legal semiotics and a comparison approach to analysing primary and secondary legal material from the statute, Ibn Qudamah’s book, and others. This article will qualitatively discuss the object of the research descriptively; and Results: Found several similarities, including: the understanding of bankruptcy, the exclusion of debtors, preferential rights, types of creditors, to the delayment of debt payment obligations. Some of the differences include: bankruptcy status; the presence or absence of bankruptcy revocation; the absence of recommendations for creditors to grant a payment delay during the debtor’s difficult times; to differences in paradigms between anthropocentric and theocentric materialism. Might this finding contribute to lighten the load of Islamisation of knowledge, as several provisions are already analogous to “Ahkam Iflas,” conjecturally derived from prophetic tradition. INDONESIA Permasalahan Utama Penelitian: Artikel ini berawal dari temuan kesamaan para peneliti sebelumnya, seperti temuan Lubis bahwa berbagai ketentuan kepailitan dalam Bidayatu Al-Mujtahid serupa dengan Hukum Kepailitan Indonesia, dan peraturan kepailitan Barat (tradisi hukum Common Law dan Civil Law Eropa Kontinental) seperti temuan Abed dan Michael dalam penelitian mereka, ketentuan kepailitan Al-Mughni (karya Ibn Qudamah) serupa dengan Undang-Undang Kepailitan Amerika Serikat. Untuk itu, ada baiknya meneliti Hukum Kepailitan Indonesia dibandingkan dengan fikih Ibn Qudamah; Tujuan Penelitian: Untuk menemukan ketentuan hukum kepailitan post-modern yang similar dan mirip dengan hukum kepailitan Islam “ahkam iflas” yang dibahas dalam kitab Ibn Qudamah sejak delapan abad sebelumnya. Secara khusus, untuk menyingkap bagaimana substansi hukum Iflas dalam karya ahli hukum tersebut dibandingkan dengan Undang-Undang No. 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang; Metodologi: Menggunakan pendekatan legal-semiotika dan perbandingan untuk menganalisis bahan hukum primer dan sekunder dari undang-undang, buku Ibn Qudamah, dan lainnya. Artikel ini akan membahas objek penelitian secara deskriptif dan kualitatif; dan Hasil: Ditemukan beberapa kesamaan, termasuk: pengertian kebangkrutan, pengecualian debitur, hak preferensial, jenis kreditur, hingga penundaan kewajiban pembayaran utang. Beberapa perbedaannya meliputi: status kebangkrutan; ada atau tidaknya pencabutan kebangkrutan; tidak adanya rekomendasi bagi kreditur untuk memberikan penundaan di masa-masa sulit debitur; dan perbedaan paradigma antara materialisme antroposentris dan teosentris. Seomga temuan ini berkontribusi untuk meringankan beban tugas Islamisasi pengetahuan, karena beberapa ketentuan hukum kepailitan sudah sesuai dengan ahkam Iflas,, diduga berasal dari tradisi profetik.